HOW TO COPE WITH DEPRESSION (Ustozlar uchun, 2026)
This article explores the issue of depression and provides practical strategies for coping with it. It explains the main symptoms and causes of depression, emphasizing that it is a serious mental health condition rather than a temporary emotional state. The article discusses various methods to manage depression, including seeking professional help, building a support system, and maintaining a healthy lifestyle. Overall, the article aims to raise awareness about depression and encourage individuals to take proactive steps toward recovery. It promotes the idea that with the right support and strategies, it is possible to overcome depression and lead a fulfilling life.